OPTIMASI HASIL MELON (Cucumis melo, L) PADA TANAH PODSOLIK MERAH KUNING DENGAN MENGGUNAKAN PUPUK BIO ORGANIK - SURTINAH SURTINAH; SEPRITA LIDAR (Universitas Lancang Kuning, 2019)
Red Yellow Podsolic Soil (FMD) is a type of soil that dominates soil conditions in Pekanbaru, PMK soil with low fertility will be a limiting factor in increasing crop production. Melon is a horticultural plant that requires fertile and loose soil. Herbafarm is one of the bioorganic fertilizers that can cover the shortage of PMK land to increase its productivity. The treatment design tested was Herbafarm concentration consisting of H1 = without herbaceous; H1 = herb 2 ml liter-1 water; H2 = 4 ml liter-1 water; H3 = 6 ml liter-1 water; and H4 = 8 ml liter-1 water. The environmental design used is a completely randomized design. Data analysis uses a polynomial regression. Bio Organic Concentration Herbafarm which gives growth and melon yield is 6.8 ml liter-1 water, with an optimal fruit weight of 1683.08 grams.